Does Auditing Quality Mitigate Investors’ Overpriced Behaviour? Evidence from The Chinese A-Share Market - Ling Zhang; Chao Ge; Wun-Hong Su (STIE Malangkucecwara, 2017)
One of the most significant empirical findings of the auditing literature is that high auditing quality affects investor sentiment towards asset prices. Auditing quality includes auditor reputation and accounting information. Prior studies (e.g., Baker & Wurgler, 2006) document that the shares of certain firms that are inherently difficult to value are more affected by shifts in investor sentiment. Using a sample of 58,476 observations from the Chinese a-share market over the 2009-2014 period, this study examines whether auditing quality mitigates the impact of investor sentiment on mispricing behaviour. The empirical results demonstrate that sentiment-related mispricing is in fact diminished in firms with auditor reputation. Investors pay a lower price for the difficult-to-value firms. By contrast, accounting information fails to mitigate the impact of investor sentiment on mispricing behaviour. The shares of difficult-to-value firms remain to be overpaid by investors. This study uses different proxy variables for auditor reputation and financial information. The results of this study demonstrate that the financial information of auditing quality fails to effectively correct the mispricing behaviour. On the contrary, the reputation of auditing quality correct the mispricing effectively by the signal transmission. The reputation signal of top 4 international accounting firms is slightly stronger than top 10 Chinese accounting firms.